Categorical Nature of Consumer Price Estimations of Postharvest Bruised Apples - Yasushi Kyutoku; Naoko Hasegawa; Ippeita Dan; Hiroaki Kitazawa (Journal of Food Quality)
Postharvest fruits are susceptible to damage which eventually results in large product and financial losses. While abundant studies have been conducted to objectively index the severity of such damage, how consumers subjectively assess the severity of damaged apples has been understudied. Previous studies have indicated that consumers’ aesthetic devaluation of product quality is reflected in estimated price. Thus, the current online questionnaire study was conducted to examine the effect of objectively indexed severity of damage on consumers’ subjective price estimations. Four hundred thirty-nine consumers of apples were asked to estimate the market price for apples in photographic images of 1 or 3 “Orin” (“Golden Delicious” × “Indo”) apples at 9 levels of severity of damage. A 2 (1- and 3-piece) × 9 (severity of damage) within ANCOVA with reference price as a covariate indicated significant two-way interaction between the number of apples and severity of damage on estimated price. Consequently, the 1- and 3-piece conditions were examined separately. The results of both analyses indicate a categorical rather than quantitative, continuous reduction in estimated price.